Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.5581/1516-8484.20120092
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of anemia of blood donor candidates deferred by hematologic screening

Abstract: Objective: Iron deficiency is the most common cause of anemia and one of the main factors in the clinical deferral of blood donors. This fact prompted the current study that aimed to determine the prevalence and etiology of anemia in blood donor candidates and to evaluate the hematological screening technique used for the exclusion of these donors. Methods: This was a prospective study that compared two groups (Anemic and Non-anemic). Initially screening for anemia was performed by manually measuring hemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
1
13
1
Order By: Relevance
“…This may have resulted in a selection bias against females consequently influencing the true representation of the prevalence of anaemia in this group. The finding of fewer female donors in this study corroborate with work done by Silva et al [13]. In this study, the prevalence of anaemia was observed to be higher in participants of 20 years and below irrespective of gender.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This may have resulted in a selection bias against females consequently influencing the true representation of the prevalence of anaemia in this group. The finding of fewer female donors in this study corroborate with work done by Silva et al [13]. In this study, the prevalence of anaemia was observed to be higher in participants of 20 years and below irrespective of gender.…”
Section: Discussionsupporting
confidence: 93%
“…A high prevalence of 31.44% was observed in this study. The prevalence was higher compared to the 16% reported in Nigeria [18], 4.2% in Brazil [13], and 1.8% in India [19]. The difference between the prevalence of anaemia in these studies compared to ours could be attributed to the differences in the nutritional habits of these populations.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The normal daily iron intake is around 15 mg, with only a small proportion of this being absorbed . This makes it difficult for regular blood donors to sustain iron levels, and low Hb is a common cause of deferral from donation . In theory, LGI should lead to slightly higher levels of hepcidin and thus be associated with lower Hb levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications have suggested that serum ferritin levels could be a reliable indicator for body iron stores since they provide a determination of iron deficiency at an early stage (11,12) . …”
mentioning
confidence: 99%